THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT ON JOB PERFORMANCE (Study at The Main Office of PT. Bank SulutGo Manado) - Paruntu, Sharon Gestia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Job performance is an important thing that has to be noticed by the management of the company. In this case, in improving their job performance. The management of the company is not only thinking about how to achieve the goals of the company, but also think about the sake of the employees themselves. The employees are not only working for the company, but they are also working to fulfill the needs as their obligation and responsibility to their family. That is why, the organizational support is really important thing to increase the job performance of employee. This study aims to determine the influence of perceived organizational support on job performance. It was conducted at the main office of PT. Bank SulutGo Manado that used 100 respondents. This research is quantitative research that use Multiple Linear Regression analysis to analyse the data. This study recommends PT. Bank SulutGo to maintain and even increase the organizational commitment and job involvement, because the result shown that the organizational commitment and job involvement gives significant influence on job performance. Keywords: perceived organizational support, job performance